Life cycle tribology : Proceedings of the 31st Leeds-Lyon Symposium on Tribology, held at Trinity and All Saints College, Horsforth, Leeds, UK, 7th-10th September 2004 /: Proceedings of the 31st Leeds-Lyon Symposium on Tribology, held at Trinity and All Saints College, Horsforth, Leeds, UK, 7th-10th September 2004. ([2014?]) - Unknown
No abstract available